The relationship between relative lower-body strength, sprint and change of direction ability in elite youth female soccer athletes - De Marco, K.; Lyons, M.; Joyce, C.; Conlon, J. A. (International Journal of Sports Science & Coaching, 2023)
Soccer is described as a high-intensity, multidirectional sport requiring athletes to possess a high level of physical conditioning to compete at the elite level. Strength, linear sprint and change of direction (COD) abilities are key physical characteristics in soccer-specific performance, with research suggesting athletes who possess greater relative lower-body strength are superior in sprint and COD ability. The purpose of this study was to investigate the relationship between relative lower-body strength with linear sprint and COD ability among elite youth female soccer athletes in Western Australia. Forty-four (U13, n = 11; U14, n = 12; U15, n = 11; U19, n = 10) athletes completed an isometric mid-thigh pull (IMTP), 30 m sprint and 505 COD test. Results demonstrated a significant moderate correlation between relative IMTP (IMTPr) performance and 10 m (r = -0.315, p = 0.037) and 30 m (r = -0.0347, p = 0.021) sprint time, however, there was no significant correlation between IMTPr performance and COD deficit (r = -0.227, p = 0.168). This study suggests that relative lower-body strength is moderately related to greater sprint performance but not COD ability in elite youth female soccer athletes. Overall, relative lower-body strength appears to be advantageous to linear sprint performance in elite youth female soccer athletes, and therefore the inclusion of appropriate and targeted strength training in the physical preparation and long-term athlete development of this demographic may be recommended.